Contemporary Readings of Sahih Al-Bukhari Its Schools, its Starting Points, Examples of its Challenges at Sahih: القراءات المعاصرة لصحيح البخاري مدارسها، منطلقاتها، أمثلة على طعونها في الصحيح - Halim, Medebbeur (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
يُعتبر صحيح البخاري أهم مرجعٍ حديثي عند أهل السنة، وبهذا تظهر أهمية الدراسة المتعلقة به، وكان الصحيح ذا منزلةٍ عاليةٍ على مر العصور، لكن في العصر الحديث بدأ الخوض فيه من جهة عدم صلاحية أحاديثه في الاحتجاج، وهذه الورقة العلمية سترصدُ معالم القراءات المعاصرة له، ببيان مناهجها، وأنواعها، وأصول استمدادها. وتكمن أهمية الدراسة من جهة الحاجة لمعرفة هذه القراءات المعاصرة رصداً لها وابرازاً لدورها في الطعن في الصحيح خصوصاً، والسنة النبوية عموماً. واعتمدت الورقة على المنهج الاستقرائي التحليلي بجمع المعطيات، وتحليلها حسب طبيعة الدراسة، مع استخدام المنهج الاستنباطي بأخذ تصورٍ شاملٍ لهذه القراءات المعاصرة. وتتجلي مشكلة الدراسة في توجه القراءات المعاصرة لصحيح البخاري طعناً وقدحاً فيه، وهذه القراءات تعددت مناهجها واستمداداتها، والصور التطبيقية لطعن هذه المدارس في صحيح البخاري، وللإجابة عن ذلك كان لابُدَّ من وضع أربعة مطالب فيها، وهي: منزلة صحيح البخاري عند أهل الحديث، ونشوء القراءات المعاصرة لصحيح البخاري، وأهم المدارس المعاصرة الطاعنة في صحيح البخاري، وصور من قراءة المعاصرة لبعض احاديث صحيح البخاري، وأخيرا الخاتمة مع النتائج والتوصيات. وتتمثل نتائج الورقة في وجوب العناية بكل علوم السنة، وتكثيف الدراسات حول صحيح البخاري، والدعوى لإنشاء مركز علمي عالمي لرصد القراءات المعاصرة للسنة ومواجهتها. الكلمات المفتاحية: السنة النبوية، صحيح البخاري، القراءات المعاصرة، الطعن في الحديث النبوي. Abstract Sahih al-Bukhari is considered the most important hadith reference among Sunnis, and by this the importance of the study related to it appears, and the sahih has been of high standing throughout the ages. But in the modern era, he began to delve into it in terms to the inappropriateness of his hadiths in protest, and this scientific paper will monitor the features of contemporary readings by stating their methods, types, and derivation. The importance of the study: on the one hand the need to know these contemporary reading to monitor them and highlight their role in challenging the Sahih and the Sunnah in general. Methodology of the study: the paper relied on the inductive analytical method by collecting data and analyzing it according to the nature of the study. With the use of the deductive method by taking a comprehensive view of these contemporary readings. Problem the study: what are the most important contemporary readings of Sahih al-Bukhari as a stab and insult? What are types, methods, and derivation of these readings? What are the applied images outlined in the appeal against Sahih al- Bukhari? To answer this, it was necessary to develop five sections. Namely: the status of Sahih al-Bukhari among the people of hadith, the emergence of contemporary readings of Sahih al-Bukhari, the most important contemporary schools of contention in Sahih al-Bukhari, pictures of conclusion with findings and recommendations. The results of the paper are represented in the necessity to pay attention to all the sciences of the Sunnah, to intensify studies on Sahih al- Bukhari, and the call to establish a global scientific center to monitor and confront contemporary readings of the Sunnah. Keywords: Prophetic Sunnah, Sahih al-Bukhari, Contemporary readings, Challenging Prophetic Hadith.